Prosthetic stomatitis in patients with diabetes mellitus: correction of psycho-emotional stress - V.M. Dvornyk; I.Yu. Lytovchenko; I.Yu. Popovych; I.A. Holovanova; I.L. Dvornyk; O.V. Muravlova; L.B. Yerus; O.I. Teslenko (Medičnì Perspektivi)
A high level of chronic emotional stress affects the occurrence and increases the severity of diseases of the oral mucosa and internal pathology. The aim of the work is to increase the effectiveness of the treatment of prosthetic stomatitis in patients with diabetes mellitus against the background of psycho-emotional stress by correcting it. To objectify the state of psycho-emotional stress, in 2005-2015 and in 2022 psychological testing was carried out by the D. Taylor method on 230 people aged 19-70 years, among whom 85 patients were diagnosed with diabetes mellitus – the main group; 145 people were without internal diseases – two control groups. General examination and treatment of patients of the main group – 46 women and 39 men aged 19-70 years was carried out by endocrinologists according to the relevant protocols. Dental examination and treatment of prosthetic stomatitis was carried out in 12 patients with diabetes mellitus who had a high level of general anxiety according to the D. Taylor method. Own method of treatment: after the correction of the prosthesis, sanitation of the oral cavity, applications of thiotriazoline 2% ointment, a course of 7-10 days on the areas of the prosthetic bed, most often subject to trauma were prescribed. For general therapy, an additional stress-protective drug which corrects psycho-emotional stress in patients with diabetes mellitus was prescribed, thiotriazoline, orally, for 30 days. In patients of the main group, a high level of general personal anxiety was recorded in 21.63% of respondents and an average level with a tendency to high – in 54.29%. In many cases, the dentist should know the level of the patient's psycho-emotional stress in order to justify an individual approach to therapeutic measures and maintenance therapy in the choice of drugs and methods. The proposed method of treatment of prosthetic stomatitis has an individual approach, includes the stress-protective drug thiotriazoline, which corrects psycho-emotional stress, allowing to achieve a stable remission of the disease.